Fire Sales and the Financial Accelerator - Choi, Woon (IMF Working Papers; Working Paper ;, 2010)
During periods of financial turmoil, increases in risk lead to higher default, foreclosure, and fire sales. This paper introduces a costly liquidation process for foreclosed collateral and endogenous recovery rates in a dynamic stochastic general equilibrium model of the financial accelerator. Consistent with empirical evidence, we find that recovery rates are pro-cyclical when collateral is costly to liquidate. Through links between recovery rates, risk premia, and default risk, the model generates an additional liquidity spiral, a feedback loop for the financial accelerator. We illustrate how collateral liquidation and monetary policy alter the impacts of a financial shock. We also show that a government subsidy on collateral liquidity and the endogenous accumulation of liquidity inventory help dampen the liquidity spiral by shoring up recovery rates.